2016
DOI: 10.1161/hypertensionaha.116.07232
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Interactions Between Carotid Baroreceptors and Chemoreceptors in Obesity Hypertension

Abstract: Carotid bodies play a critical role in protecting against hypoxemia and their activation increases sympathetic activity, arterial pressure and ventilation, responses opposed by acute stimulation of the baroreflex. While chemoreceptor hypersensitivity is associated with sympathetically-mediated hypertension, the mechanisms involved and their significance in the pathogenesis of hypertension remains unclear. We investigated the chronic interactions of these reflexes in dogs with sympathetically-mediated, obesity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…84 Carotid baroreflex activation has been shown to reduce blood pressure, heart rate, and plasma norepinephrine in this model. 84,85 A blunted sympathetic baroreflex has been observed in both clinical and experimental obesity, 86,87 and weight loss is associated with an improvement in sympathetic baroreflex function. 55 Grassi and colleagues have further demonstrated that the association between obesity and hypertension is associated with impairment in both sympathetic and vagal baroreflex cardiovascular control and that the magnitude of impairment is greater in those with combined obesity-related hypertension than in those with either obesity or hypertension alone.…”
Section: Sympathetic Activity In Human Obesitymentioning
confidence: 76%
“…84 Carotid baroreflex activation has been shown to reduce blood pressure, heart rate, and plasma norepinephrine in this model. 84,85 A blunted sympathetic baroreflex has been observed in both clinical and experimental obesity, 86,87 and weight loss is associated with an improvement in sympathetic baroreflex function. 55 Grassi and colleagues have further demonstrated that the association between obesity and hypertension is associated with impairment in both sympathetic and vagal baroreflex cardiovascular control and that the magnitude of impairment is greater in those with combined obesity-related hypertension than in those with either obesity or hypertension alone.…”
Section: Sympathetic Activity In Human Obesitymentioning
confidence: 76%
“…49 However, this has not been our experience when using the Barostim Neo system during chronic bilateral carotid sinus activation in canines. 33,50 Randomized controlled trials are needed to thoroughly evaluate whether the Barostim Neo electrode system may have clinical utility in managing RHT.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is strongly linked to cardiometabolic comorbidities including hypertension, diabetes mellitus, and obstructive sleep apnea. 79,80 Similarly, increasing body mass index is related to increased risk of AF. 2 Interventions to reduce body weight have numerous positive health effects in AF patients, including BP reduction, decrease in glucose, total cholesterol, low-density cholesterol, and triglycerides, inhibition of inflammation (eg, reduction in C-reactive protein levels), attenuation of pathological LA remodeling (ie, decrease in LA volume) and LV remodeling (reduction of LV hypertrophy and E/eʹ ratio).…”
Section: Impact Of Physical Activity and Obesitymentioning
confidence: 99%